Desafios na Implantação da Depreciação de Bens Móveis em uma Instituição Federal de Ensino no Espírito Santo - Delazare, Elika Capucho (2021)
The recognition of the depreciation in the statement of financial position of federal educational has become mandatory since the Law nº. 4.320/1964 and, more recently, with the Brazilian Accounting Standards Applied to the Public Sector, published in 2008 in force for events occurring as of 2010. Thus, this research had as a general objective to identify what are the challenges that are presented for the implementation of the depreciation of assets in a federal educational institution. For this, an exploratory research was conducted, with a qualitative approach and use of the field research method. The research was conducted at the Federal Institute of Espírito Santo (IFES) and used a questionnaire applied to Coordinators of Assets, Accounting Coordinators, and Directors of Administration and Planning of the 22 campi, in addition to servers of the Dean of Administration and Budget, this area responsible for preparing the budget proposal of the institution, thus composing a group of 71 servers, with participation in the research of 52.11%. The research also analyzed the inventory of the IFES Serra Campus, using an electronic spreadsheet. Furthermore, the research was based on the Institutional Theory, under the aspect of institutionalization phases. The results of the research showed that the difficulty most cited by the servers, 81.08%, was the absence or deficiency to the asset management system. Still, most of the interviewees, 89.19%, identify that the depreciation mechanism brings managerial and budgetary benefits and, 97.30%, see social benefits. As for the result of the analysis of the inventory of the IFES Serra Campus, it showed that 61.20% of the value with property, plant and equipment of the unit would already be depreciated. Despite the efforts of IFES to comply with the legislation it is still necessary to go a long way for the effective depreciation of total assets.